2017
DOI: 10.20517/2394-5079.2017.07
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p53 in extrinsic factor-induced liver carcinogenesis

Abstract: How to cite this article: Link T, Iwakuma T. Roles of p53 in extrinsic factor-induced liver carcinogenesis. Hepatoma Res 2017;3:95-104.Liver cancer remains one of the most common human cancers with a high mortality rate. Therapies for hepatocellular carcinoma (HCC) remain ineffective, due to the heterogeneity of HCC with regard to both the etiology and mutation spectrum, as well as its chemotherapy resistant nature; thus surgical resection and liver transplantation remain the gold standard of patient care. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 125 publications
(122 reference statements)
1
23
0
Order By: Relevance
“…Accumulating evidence demonstrated that tumor suppressor genes (TSGs) closely regulate cell proliferation and differentiation, as well as lipid metabolisms and NAFLD. TP53, a TSG and one of the most frequently mutated genes in HCC, inhibits the expression of cellular metabolism-regulating genes to prevent tumor development [6]. Liver-specific deficiency of PTEN, another well-known TSG, promotes hepatic expression of adipocyte-specific genes and lipogenesis and beta-oxidation-related genes [7], leading to steatohepatitis and HCC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence demonstrated that tumor suppressor genes (TSGs) closely regulate cell proliferation and differentiation, as well as lipid metabolisms and NAFLD. TP53, a TSG and one of the most frequently mutated genes in HCC, inhibits the expression of cellular metabolism-regulating genes to prevent tumor development [6]. Liver-specific deficiency of PTEN, another well-known TSG, promotes hepatic expression of adipocyte-specific genes and lipogenesis and beta-oxidation-related genes [7], leading to steatohepatitis and HCC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Non-alcoholic steatohepatitis (NASH), involving mechanisms such as upregulation of TP53 activity with increased mRNA levels of the p21 and p66ShC proteins, which are associated with fibrosis severity (33). The current study also identified somatic mutations in other known HCC driver genes, including beta-catenin (CTNNB1),, ARID1A, ARID2, AXIN1, among others.…”
mentioning
confidence: 71%
“…(31,32) Etiological factors, in addition to AFB 1 ,such as HBV, HCV and alcohol have been implicated in generating TP53 mutations in HCC. (31,33) Inactivation of p53 by core proteins produced by HBV (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no effective treatment for HCC due to the high heterogeneity of the cancer. Thus, extrinsic factors and different mutations contribute to the induction of liver cancer [3,4]. Among the genetic factors, mutations in the p53 tumor suppressor gene (TP53) are frequent, especially in HCC from populations exposed to environmental carcinogens, such as dietary aflatoxin B1 [5].…”
Section: Introductionmentioning
confidence: 99%